2011
DOI: 10.1002/icd.730
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of scientific knowledge: the influence of methods of questioning and analysis on the interpretation of children's conceptions of the earth

Abstract: International audienceStudies of children’s knowledge of the Earth have led to very different conclusions: some appear to show that children construct their own, non-scientific ‘theories’ (mental models) of the flat, hollow or dual Earth. Others indicate that many young children have some understanding of the spherical (scientific) Earth, and that their knowledge lacks the coherence of mental models. The reasons for these contrasting views were tested by interviewing French children (N5178) aged 5–11 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
15

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 21 publications
2
20
1
15
Order By: Relevance
“…Nevertheless, research has shown that variations in methodology and interview technique can influence the range of mental models elicited (see Frède et al 2011;Nobes et al 2003;Panagiotaki et al 2006;Schoultz et al 2001). This suggests that children's cosmologies are richer than the categorisation systems used to classify them.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, research has shown that variations in methodology and interview technique can influence the range of mental models elicited (see Frède et al 2011;Nobes et al 2003;Panagiotaki et al 2006;Schoultz et al 2001). This suggests that children's cosmologies are richer than the categorisation systems used to classify them.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are supported by primary‐school children's competencies in ToM, demonstrating that children even as young as primary‐school age are able to grasp the idea of active mental construction and, as the advanced ToM literature shows, possess a nascent understanding of interpretative frameworks and perspectives (Carpendale & Chandler, ; Pillow, ). Furthermore, children performed slightly better on the MS items than in the open‐ended interview (Bullock et al ., ; Frède et al ., ; Pollmeier et al ., ). It seems that presenting children with a choice of answers and asking them to select the best one (in MC tests), or asking them to reflect on each proposition (of different levels) and to accept or reject it (in MS tests) helped the children to structure their ideas.…”
Section: Discussionmentioning
confidence: 96%
“…Frède et al . () claim that these differences might not be attributable solely to the production–recognition distinction but also to the fact that the requirements of a task are conveyed more clearly by forced‐choice questions (as in this MS format) than by open‐ended questions (as in interviews). This finding suggests strongly that low verbal abilities together with uncertainty about the requirements of an open‐ended question can negatively influence the interview score.…”
Section: Discussionmentioning
confidence: 99%
“…The fi ndings of the other studies with Greek, Chinese, New Zealand, and Australian children supported Vosniadou and colleagues' claims that children have intuitive and synthetic mental models of the earth and children's understanding of the shape of the earth is constrained by their presuppositions Hayes et al, 2003 ;Kallery, 2011 ;Tao et al, 2012 ). However, the fi ndings of recent studies with Swedish, English, Australian, French, Estonian and Dutch children have challenged the Vosniadou and colleages' claims that children's understandings of the shape of the earth are coherent and constrained by presuppositions (e.g., Frède et al, 2011 ;Hannust & Kikas, 2007Nobes et al, 2005 ;Schoultz et al, 2001 ;Siegal et al, 2004 ;Straatemeier et al, 2008 ). The results of these studies suggested that even the preschoolers have a scientifi c understanding of the shape of the earth and these studies reported that there was little evidence for the naive and synthetic mental models of the earth, and children's understanding of the earth is likely to be fragmented rather than coherent.…”
Section: Summaries Of Children's Understanding Of Space Science Conceptsmentioning
confidence: 99%